FUNGSI SHOFAR DALAM PERIBADATAN DI GJKI MILLENIUM DAMAI MINISTRI SURAKARTA - Yona Ari Prihandhini; Sigit Astono (Institut Seni Indonesia Surakarta, 2021)
This paper describes the function of shofar at GJKI Millennium Damai. This qualitative research generally based on Malinowski's theory, and contextually based on Merriam’s theory. Qualitative research data were collected through interviews, literature studies, and observations of the previous worship documentation videos. The results of the study show that, spiritual needs of GJKI Millennium Damai’s concegeration which embrace the tabernacle of Mose is an impulse, then the act is using shofar, the result is spiritual satisfaction. Contextually function of shofar first, that the function of the Shofar in worship is as as a vertical communication medium between the servant and the God. Second, the function of the Shofar plays, believed that the sound of the Shofar makes God's presence more pronounced, so the concegration responded such as crying, clapping, dancing and so on. Third, shofar as a validation of religious rituals, in accordance with the recommendations of the Exodus Bible, which contains the concept of Mose’s tabernacle and is believed to be true by the GJKI Millennium Damai.